1984
DOI: 10.1002/qj.49711046607
|View full text |Cite
|
Sign up to set email alerts
|

Structure and evolution of a mesoscale convective system near the British Isles

Abstract: SUMMARYFrequent digital cloud imagery from Meteosat and precipitation patterns from radar have been analysed together with surface observations and conventional and satellite soundings, to develop a conceptual model of a small mesoscale convective system. The system, observed to the south-west of England, had many of the features previously found in the United States, where the term mesoscale convective system or complex is applied to a cluster of thunderstorms that generates a common cirrus shield of mesoscal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 5 publications
3
26
0
Order By: Relevance
“…Analyses of such events have revealed that the moist downdraughts sometimes do not penetrate to the surface through the large-scale low-level layer of cool air, e.g. Browning and Hill (1984) for a MCS in the UK, and Fortune et al (1992), Smull and Augustine (1993) and Trier and Parsons (1993) for large MCSs (Mesoscale Convective Complexes) in the USA. This was true also in the present case.…”
Section: Introductionmentioning
confidence: 99%
“…Analyses of such events have revealed that the moist downdraughts sometimes do not penetrate to the surface through the large-scale low-level layer of cool air, e.g. Browning and Hill (1984) for a MCS in the UK, and Fortune et al (1992), Smull and Augustine (1993) and Trier and Parsons (1993) for large MCSs (Mesoscale Convective Complexes) in the USA. This was true also in the present case.…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenology of extratropical cyclones and frontal systems is well depicted and understood in terms of conceptual models for higher European latitudes, and mesoscale convective systems have also been studied in the north Atlantic. Browning & Hill (1984) studied the development and evolution of a mesoscale convective system near the British Isles, in terms of Meteosat imagery, radar data and conventional meteorological soundings, and developed a conceptual model that recognises four stages of evolution. Local scale thunderstorms were studied in north-west Europe by Collier & Lilley (1994) addressing the initiation forecasting problem.…”
Section: Introductionmentioning
confidence: 99%
“…Mesoscale convective systems (MCSs), that is, systems of cloud and precipitation that include at least one thunderstorm cell during most of their lifetime (Zipser 1982), occur in a continuous spectrum from small, shortlived systems (e.g., Browning and Hill 1984;Knupp and Cotton 1987;Yuter and Houze 1995a) to long-lived mesoscale convective complexes (MCCs) exhibiting an average maximum area 1 of approximately 160 ϫ 10 3 km 2 and a lifetime of about 13 h (e.g., Maddox et al 1982). Figure 1 presents area and lifetime values for 161 MCCs observed over the United States for the 1985-87 period.…”
Section: Introductionmentioning
confidence: 99%